Use of computer technology for English language learning: do learning styles, gender, and age matter?. Issue 5 (3rd July 2016) - Lee, Cynthia; Yeung, Alexander Seeshing; Ip, Tiffany
Abstract : Computer technology provides spaces and locales for language learning. However, learning style preference and demographic variables may affect the effectiveness of technology use for a desired goal. Adapting Reid's pioneering Perceptual Learning Style Preference Questionnaire (PLSPQ), this study investigated the relations of university students' learning styles and the use of computer technology for language learning, and whether the demographic variables of gender and age would make a difference. Chinese students aged 17–36 years ( M = 20.31, SD = 3.42) from two universities in Hong Kong ( N = 401: male = 140 and female = 261) responded to a survey about four learning styles and computer technology. Principal components analysis and confirmatory factor analysis established the five factors, which were all positively correlated. No gender differences were found in technology application and learning styles (visual, auditory, kinesthetic, and tactile). Only some subtle age differences were found in kinesthetic and tactile styles but not in technology use. Structural equation modeling found significant relations of computer use with visual and kinesthetic learning styles but not auditory and tactile styles. Evidence points to the benefit of helping the learners to discover their own learning styles, and optimizing learners' visual and kinesthetic learning for the use of computer resources and activities for language learning.